CU ISOTOPIC FRACTIONATION IN THE SUPERGENE ENVIRONMENT WITH AND WITHOUT BACTERIA - Mathur R.; Ruiz J.; Titley S.; Liermann L.; Buss H.; Brantley S. (My University, 2005)
The isotopic composition of dissolved Cu and solid Cu-rich minerals [δ65Cu (‰) = (65Cu/63Cusample/65Cu/63Custd) - 1)*1000] were monitored in batch oxidative dissolution experiments with and without Thiobacillus ferrooxidans. Aqueous copper in leach fluids released during abiotic oxidation of both chalcocite and chalcopyrite was isotopically heavier (δ65Cu = 5.34‰ and δ65Cu = 1.90‰, respectively, [±0.16 at 2σ]) than the initial starting material (δ65Cu = 2.60 ± 0.16‰ and δ65Cu = 0.58 ± 0.16‰, respectively). Isotopic mass balance between the starting material, aqueous copper, and secondary minerals precipitated in these experiments explains the heavier isotopic values of aqueous copper. In contrast, aqueous copper from leached chalcocite and chalcopyrite inoculated with Thiobacillus ferrooxidans was isotopically similar to the starting material. The lack of fractionation of the aqueous copper in the biotic experiments can best be explained by assuming a sink for isotopically heavy copper present in the bacteria cells with δ65Cu = 5.59 ± 0.16‰. Consistent with this inference, amorphous Cu-Fe oxide minerals are observed surrounding cell membranes of Thiobacillus grown in the presence of dissolved Cu and Fe.